2011
DOI: 10.1017/s1366728910000490
|View full text |Cite
|
Sign up to set email alerts
|

The receptive–expressive gap in the vocabulary of young second-language learners: Robustness and possible mechanisms

Abstract: Adults and children learning a second language show difficulty accessing expressive vocabulary that appears accessible receptively in their first language (L1). We call this discrepancy the receptive-expressive gap. Kindergarten Spanish (L1) -English (L2) sequential bilinguals were given standardized tests of receptive and expressive vocabulary in both Spanish and English. We found a small receptive-expressive gap in English but a large receptive-expressive gap in Spanish. We categorized children as having had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
105
2
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(128 citation statements)
references
References 37 publications
12
105
2
9
Order By: Relevance
“…Furthermore, in light of the results showing that the challenges of L2 learners are particularly severe on expressive skills in the second language (Gibson et al, 2012), the children in our study may have had a greater potential for change in expressive skills. If we compare our results to other findings, the lack of effects on receptive language measures has also been the case in other studies on dialogic reading using a similar receptive vocabulary measure (PPVT-R; Dunn & Dunn, 1981;Whitehurst et al, 1994;Whitehurst et al, 1988).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Furthermore, in light of the results showing that the challenges of L2 learners are particularly severe on expressive skills in the second language (Gibson et al, 2012), the children in our study may have had a greater potential for change in expressive skills. If we compare our results to other findings, the lack of effects on receptive language measures has also been the case in other studies on dialogic reading using a similar receptive vocabulary measure (PPVT-R; Dunn & Dunn, 1981;Whitehurst et al, 1994;Whitehurst et al, 1988).…”
Section: Discussionmentioning
confidence: 75%
“…Based on the rationale of a unitary core language construct, the most effective intervention to improve children's global language skills will presumably be to cover several aspects of language and include both expressive and receptive vocabulary, grammar, and syntax. However, although studies of monolingual children show that expressive and receptive language are highly related skills, it has been shown that the challenges for second-language learners are particularly significant in the area of expressive skills in the second language (Gibson, Oller, Jarmulowicz, & Ethington, 2012). This result speaks for having a particular focus on expressive language in an intervention.…”
Section: Theoretical Framework For Designing a General Language Instrmentioning
confidence: 99%
“…The PPVT-III was selected over the more recent PPVT-IV because it is closer in form to the TVIP, which was adapted from the PPVT-R, but still represents improvements over the PPVT-R in reducing cultural bias. This combination of the PPVT-III and the TVIP has been used in recent studies of receptive vocabulary in Spanish-English bilingual children (e.g., Gibson et al, 2012; Hammer et al, 2008). To measure English expressive vocabulary, all children completed the Picture Vocabulary subtest of the Woodcock-Johnson III Tests of Achievement (Form A) (Woodcock, McGrew, & Mather, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…For example, Hammer and colleagues (Hammer, Lawrence, & Miccio, 2008) documented differences between simultaneous and sequential bilinguals in their English and Spanish receptive vocabulary scores at the beginning and end of a two-year period in Head Start. During the school-age years, a phenomenon of shifting dominance has been documented in sequential bilinguals such that a gap emerges between their receptive and expressive skills in the home language, with continued receptive development and plateaued expressive skills (Gibson, Oller, Jarmulowicz, & Ethington, 2012; Hemsley et al, 2010; Kan & Kohnert, 2005; Oller et al, 2007; Sheng et al, 2011). However, previous studies of conceptual scoring have generally investigated either simultaneous or sequential bilinguals rather than drawing direct comparisons between the two groups.…”
Section: Factors Influencing the Vocabulary Performance Of Bilingual mentioning
confidence: 99%
“…However, we would argue that this conclusion is premature and is likely to be anchored to the use of expressive measures to index morpheme-learning performance. It is well known that bilingual children tend to make expressive gains in their L2 at a slower pace than receptive gains (e.g., Gibson, Oller, Jarmulowicz, & Ethington, 2012;Gibson, Peña, & Bedore, 2014;Junker & Stockman, 2002;Kan & Kohnert, 2005;Pearson, Fernandez, & Oller, 1993;Yan & Nicoladis, 2009). Therefore, it is highly likely that their ability to apply the newly acquired derivational morpheme to words in their second language expressively is strongly linked to their overall levels of expressive ability in their second language.…”
Section: Novel Morpheme Learning In Bilingual Childrenmentioning
confidence: 99%